Pengaruh Konten Live Streaming Tiktok Shop terhadap Kenyamanan dan Dampaknya pada Keputusan Pembelian Produk Baju - Ali, Muhammad Akbar; Rapida, Ida (Ma'soem University, 2025)
The background of the problem, research objectives, research methods, as well as results and discussionThe background to this research is the increasingly competitive climate in the business world, especially clothing products. PT Jin Myoung Industrial, located in Padalarang, realizes the importance of marketing by utilizing advances in information technology. Marketing activities are not only carried out conventionally but also using social media, one of which uses Tiktok media. This study aims to analize the impact of TikTok Shop live streaming content at PT. Jin Myoung Industrial Padalarang on online consumer comfort, and its effects on purchasing decisions. Specifically, the research evaluates how the perceived comfort of consumers from watching live streaming content can influence their decision to make a purchase. The research method is quantitative with data collection techniques through distributing questionnaires to the Tiktok audience of PT Jin Myoung products. Sample collection uses total sampling or sensing where the population is the same as the sample size, namely 93 people. The research results show that Tiktok Shop live streaming content (X) has a significant effect of 72.2% on comfort (Z). Convenience (Z) has a significant effect of 77.1% on purchasing decisions (Y). And Tiktok Shop's live streaming content has a significant influence of 69.3% on purchasing decisions (Y).